NEUROFIBROMATOSIS TIPE 1 PADA ANAK DENGAN MANIFESTASI NEUROFIBROMA PLEKSIFORMIS YANG MENYERUPAI NEVUS BECKER (Media Dermato Venereologica Indonesiana, 2020)
Neurofibromatosis type 1 (NF-1) is a genetic disorder with an autosomal dominant inheritance pattern. It is caused by heterozygous mutations of the NF-1 gene located within the chromosome 17q11.2. Plexiform neurofibroma is one of several clinical manifestations that can be found in NF-1 cases. A 10-year-old girl was referred to the Dermatovenereology Clinic of Sanglah Hospital with the suspicion of Becker’s nevus. From the alloanamnesis, there were multiple blackish-brown spots in the left back since she was six months of age. Those spots have begun to thicken and protrude during the past two months. The brown spots appeared and spread into other parts of the body since the patient was four years old. Another complaint from the patient was back pain, starting at the age of 8. Histopathological examination supported the diagnosis of neurofibroma. No specific therapy was given in this case. The patient was then consulted to the orthopedic surgery department for her scoliosis. Eventually, the patient is planned to be consulted to the ophthalmology, pediatric, and neurology department for more comprehensive management.